HUBUNGAN KARAKTERISTIK MAHASISWA DENGAN BURNOUT AKADEMIK PADA MAHASISWA KEDOKTERAN - Revalita Wahab; Purnamawati Tjhin; Erita Istriana (Fakultas Kedokteran Universitas Trisakti, 2024)
Due to Covid-19 pandemic, learning process has changed and students had to adapt with massive rise of online learning. If the students could not adapt to the academic process, it will cause to a decline in academic achievement. The factors related to academic burnout that is to identified. The aim of this study is to investigate the related factors that cause academic burnout in medical education students. The cross- sectional study was conducted on 104 second year medical students of Universitas Trisakti using the School Burnout inventory-Indonesian version to assess academic burnout. Data analysis was performed using Chi-square. This research found that 62,5% of students experienced mild burnout and only 4,8% of them did not have burnout. Meanwhile 32,7% of the students experienced moderate to severe burnout. There is no relationship between age, gender, and academic achievement with academic burnout. The conclusion of this research is there was no significant relationship between age, gender, academic achievement with academic burnout. It is necessary to identify the internal and external factors that are related to burnout and academic achievement